Structural and Chemical Biology Approaches Reveal Isoform-Selective Mechanisms of Ligand Interactions in Mammalian Cryptochromes - Miller, Simon; Hirota, Tsuyoshi (Frontiers in Physiology, 2022)
Cryptochromes (CRYs) are core components of the circadian feedback loop in mammals, which regulates circadian rhythmicity in a variety of physiological processes including sleep-wake cycles and metabolism. Dysfunction of CRY1 and CRY2 isoforms has been associated with a host of diseases, such as sleep phase disorder and metabolic diseases. Accumulating evidence for distinct roles of CRY1 and CRY2 has highlighted the need for CRY isoform-selective regulation; however, highly conserved sequences in CRY ligand-binding sites has hindered the design of isoform-selective compounds. Chemical biology approaches have been identifying small-molecule modulators of CRY proteins, which act in isoform-nonselective and also isoform-selective manners. In this review, we describe advances in our understanding of CRY isoform selectivity by comparing X-ray crystal structures of mammalian CRY isoforms in apo form and in complexes with compounds. We discuss how intrinsic conformational differences in identical residues of CRY1 and CRY2 contribute to unique interactions with different compound moieties for isoform selectivity.